Hippocampal BOLD response during category learning predicts subsequent performance on transfer generalization. Issue 7 (18th October 2013) - Fera, Francesco; Passamonti, Luca; Herzallah, Mohammad M.; Myers, Catherine E.; Veltri, Pierangelo; Morganti, Giuseppina; Quattrone, Aldo; Gluck, Mark A.
Abstract To test a prediction of our previous computational model of cortico‐hippocampal interaction (Gluck and Myers [1993, 2001]) for characterizing individual differences in category learning, we studied young healthy subjects using an fMRI‐adapted category‐learning task that has two phases, an initial phase in which associations are learned through trial‐and‐error feedback followed by a generalization phase in which previously learned rules can be applied to novel associations (Myers et al. [2003]). As expected by our model, we found a negative correlation between learning‐related hippocampal responses and accuracy during transfer, demonstrating that hippocampal adaptation during learning is associated with better behavioral scores during transfer generalization. In addition, we found an inverse relationship between Blood Oxygenation Level Dependent (BOLD) activity in the striatum and that in the hippocampal formation and the orbitofrontal cortex during the initial learning phase. Conversely, activity in the dorsolateral prefrontal cortex, orbitofrontal cortex and parietal lobes dominated over that of the hippocampal formation during the generalization phase. These findings provide evidence in support of theories of the neural substrates of category learning which argue that the hippocampal region plays a critical role during learning for appropriately encoding and representing newly learned information so that that this learning can be successfully applied and generalized to subsequent novel task demands. Hum Brain Mapp 35:3122–3131, 2014. © 2013 Wiley Periodicals, Inc.